FROM EPISTEMOLOGICAL TRENDS TO CLINICAL AND EDUCATIONAL PRACTICES IN SPEECH-LANGUAGE PATHOLOGY - Keating, Nicole; Mayer-Crittenden, Chantal; Minor-Corriveau, Michele; Robillard, Manon; Belanger, Roxanne (European Scientific Journal, ESJ, 2013)
Without denying the importance of disciplinary studies, it is important to identify the role of interdisciplinary research. Although there is a division of knowledge into disciplines, the movement toward interdisciplinarity demonstrates a limitless innovation that better represents the reality of contemporary society and its beliefs. According to John Locke’s theory of the mind , one is born without innate ideas or concepts (Deigh 1994). We could assume that our knowledge is based on personal experiences and sensory perceptions. Understanding the human being is almost by necessity multidisciplinary because there is no single school of thought or discipline that can define the human being without taking into consideration the role of other disciplines. This paper will not only examine the role that interdisciplinarity plays in current research but it will also examine how speech-language pathology is innately interdisciplinarian and evidence-based. Clinical and educational practices will serve as examples to show how this field is inherently interdisciplinary.